2011
DOI: 10.1016/j.rbmo.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Abandoned by the State, betrayed by the Church: Italian experiences of cross-border reproductive care

Abstract: This paper investigates the case of Italians travelling abroad for fertility treatments as a reaction to the restrictive Italian law regulating medically assisted procreation. The acknowledgement of legal limitations provokes special feelings of abandonment while the decision to leave the country represents intentions that oppose institutional positions and results in an embodied dissent against them. The choice of destination considers legal, medical, economic, logistic and cultural matters and pertains to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 24 publications
1
35
0
3
Order By: Relevance
“…28 This might be particularly interesting for Italians since their law limits the efficiency of assisted reproduction treatment in couples with a severe male factor. 29,30 It is unlikely that letrozole increased congenital malformations, as no malformed babies were fathered during the course of letrozole treatment. 6 Additional studies have also shown that letrozole does not increase the risk of congenital malformations with ovulation induction.…”
Section: Letrozole For Azoospermia and Cryptozoospermia G Cavallini Ementioning
confidence: 99%
“…28 This might be particularly interesting for Italians since their law limits the efficiency of assisted reproduction treatment in couples with a severe male factor. 29,30 It is unlikely that letrozole increased congenital malformations, as no malformed babies were fathered during the course of letrozole treatment. 6 Additional studies have also shown that letrozole does not increase the risk of congenital malformations with ovulation induction.…”
Section: Letrozole For Azoospermia and Cryptozoospermia G Cavallini Ementioning
confidence: 99%
“…29 Therefore, approximately one-half of couples needing assisted reproduction travel abroad for fertility treatments. 30 This made the recruitment of couples for the present paper particularly difficult. Although sperm morphology is an independent characteristic with respect to concentration and motility, which, by contrast, are directly linked to each other, 13 we were compelled to recruit couples arbitrarily only on the basis of sperm concentration to avoid an excessively long study period.…”
Section: Discussionmentioning
confidence: 99%
“…There is also considerable variation across countries in the amounts donors are paid. Patients from countries such as Italy hope to receive better quality treatments abroad (Zanini, 2011;Shenfield et al, 2010), while other patients go abroad because the previous treatments they received in their country of residence failed (Shenfield et al, 2010;Culley et al, 2011). In their comparative study of patients seeking treatment abroad, Shenfield et al (2010) found evidence that supports the assumption that differences in regulations are important drivers of cross-border fertility care.…”
Section: Cross-border Reproductive Care In Europementioning
confidence: 94%